Smoking cessation among people with mental illness: A South African perspective - Tejil Morar; Lesley Robertson (South African Family Practice, 2022)
Tobacco use is recognised as a serious, worldwide public health concern. Smoking cessation is of great interest across a wide range of medical specialities, including family medicine. However, smoking cessation among people with mental illness (PWMI) has attracted scant attention in South African literature. This is despite PWMI suffering disproportionately from the damages of tobacco. The harms of smoking are not limited to physical health but extend to mental health. This article discusses the need for multifaceted smoking cessation treatments for PWMI in the public health sector, taking into consideration the prevalence and unique drivers of smoking in this population. A brief overview of patterns of tobacco use, associated harms and smoking cessation interventions in South Africa is given; all within the context of mental illness.